Betulinic Acid Nanogels: Rheological, Microstructural Characterization and Evaluation of their Anti-inflammatory Activity - Sosa-Gutierrez, Dalis S.; Toro-Vazquez, Jorge F.; Cano-Sarmiento, Cynthia; Grube-Pagola, Peter; Aparicio Saguilan, Alejandro; Torres-Palacios, Cristobal; Acosta-Osorio, Andres A.; Garcia, Hugo S. (Current Drug Delivery, 2021)
Background: Betulinic Acid (BA) is a lipophilic compound with proven beneficial results in topical inflammation. Nanogels (NG) are carriers of bioactive compounds with properties that make them good candidates to treat skin diseases. Objective: The objective of this study was to evaluate the anti-inflammatory activity of BA carried in NG.Methods: NG were composed of a nanoemulsion and a crosslinking agent (Carbopol 940®) applied at three concentrations (0.5, 1, and 1.5 %) and three activation times (6, 12 and 24 h). In order to select the optimal formulation, the NG were characterized mechanically and micro-structurally followed by evaluation of the BA anti-inflammatory activity in an in vivo model of auricular edema. We determined the edema inhibition activity as percent weight. Additionally, the anti-inflammatory activity of NG was validated through histological analysis. Results: The formulation with the best viscoelastic properties was the one prepared with 0.5% carbopol and 6 h of activation. Microstructural examination of this formulation showed mostly spherical structures with a mean diameter of 65 nm. From the evaluation of edema and the histological analyses, we established that the NG of BA produced 52% inhibition. In contrast, a conventional gel and free BA produced 28% and 19% inhibition, respectively.
Keywords: Ácido betulínico; Nanogeles; Inflamación cutánea